Advances in library management systems in response to the new challenges for their collections - Breeding, Marshall (Anuario ThinkEPI, 2014)
Libraries now have the challenge of managing a wide variety of materials, from books and journals on paper to the existing range of electronic resources. Information is packaged in various forms, and libraries must sign on to big deals as well as acquire single titles, single articles, open access works, ebooks, etc. Integrated library systems (ILS) are improving little by little to help in these tasks; various brands and models are cited.